Issues and Challenges in Indian Rural Marketing - M. MANIVANNAN (International Journal of Psychosocial Rehabilitation, 2020)
Rural markets offer a great scope for a concentrated marketing effort because of the recent increase in the rural incomes. Such incomes will increase faster because of better production and higher prices for agricultural commodities. Rural marketing is a developing concept, and the marketers have realized the opportunity of growth in the market recently. Any macro level strategy for these markets should focus on availability, accessibility and affordability. Focused attention needs to be paid to market research, key decision areas, problems and rural marketing environment, to reduce the uncertainly in dealing with these markets. This paper discusses the present scenario of Indian rural marketing, opportunities and also focuses on issues and challengesof rural marketing.